Pengaruh Molase Terhadap Pertumbuhan dan Hasil Jamur Tiram Putih (Pleurotus ostreatus) pada Media Serbuk Kayu Mahang dan Sekam Padi - Muhammad Ikhsan; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research purpose to know the effect of molases for growth and yield white oyster mushroom with sawdust of mahang and rice bran media. This research already held in mushroom house at kempas XIII street, Pandau Permai, Siak Hulu, Kampar Regency. This research conducted for 4 months from August until November 2017. This research used a completely randomized design (CRD) one factor with four replicaton. The factor various contentration of molases,      M1 = 68 cc/l, M2 = 136 cc/l, M3 = 204 cc/l, M4 = 272 cc/l, M5 = 340 cc/l and M6=408 cc/l. The result of research showed the molases with different concentraion give significanly different for various parameter, like time mycelium fullgrow in baglog, first time pinhead grow, diameter of oyster, weight of the white oyster mushroom and interval of harvest, but not significantly different for first time mycelium grow and amount of oyster.Keywords : white oyster mushroom, molases, sawdust of mahang, rice bran